Codependency, boundaries, and professional nurse caring: understanding similarities and differences in nursing practice. - Martsolf DS (Orthopaedic Nursing)
Codependency is a concept that has been written about extensively in both lay and professional literature over the past 15 years. Criticism has been raised about the use of the concept because it has been ill defined, may tend to pathologize traditional female roles, and has been used globally to describe almost any kind of interpersonal relationship. Nursing literature has addressed the concept with the same difficulties. And yet there are individuals who have grown psychologically as a result of seeking professional help for what has been termed 'codependent' behaviors. Is the use of the codependency concept a passing fad or does it have legitimacy in lending understanding in nursing practice? The purpose of this article is to help orthopaedic nurses understand the similarities and differences between professional nurse caring, professional and personal boundaries, and codependency. Appropriate strategies for promoting professional nurse caring, effective professional boundary maintenance, and decreasing behaviors related to codependency are described.